1974
DOI: 10.1017/s002217240004273x
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Escherichia coli colonizing newborn babies and their mothers

Abstract: SUMMARYMost babies are colonized by the predominant strains of Escherichia coli present in their own mother's faecal flora. Those babies who did not acquire their maternal faecal flora acquired strains of E. coli belonging to a small number of the possible serotypes. Moreover, the same serotypes were found in several babies and other mothers, suggesting spread within the ward. These few strains included some of the 0 groups which had previously commonly been found as urinary pathogens. These strains may have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…Results of the control samples were found similar to previous stud ies for: date of bowel colonization, frequency of drug resistance and relative stability of the flora [2,3,15,21]. Enterobacteria were present in the first stools of 53 children out of 60 at a mean level of 9.0 (s = 0.1); drug-resis tant enterobacteria were present in the first stools of 48 children at a mean level of 8.3 (s = 0.2); the dominant enterobacteria were drug-resistant in the first stools of 31 chil dren; drug-resistant enterobacteria reached at least level 7 in 44 children.…”
Section: General Considerationssupporting
confidence: 83%
See 1 more Smart Citation
“…Results of the control samples were found similar to previous stud ies for: date of bowel colonization, frequency of drug resistance and relative stability of the flora [2,3,15,21]. Enterobacteria were present in the first stools of 53 children out of 60 at a mean level of 9.0 (s = 0.1); drug-resis tant enterobacteria were present in the first stools of 48 children at a mean level of 8.3 (s = 0.2); the dominant enterobacteria were drug-resistant in the first stools of 31 chil dren; drug-resistant enterobacteria reached at least level 7 in 44 children.…”
Section: General Considerationssupporting
confidence: 83%
“…They were admitted to the intensive-care unit of the Pediatric Hospital of Tours (France) on the day of delivery or the day after. They were chosen for (1) presenting no digestive trouble, (2) having no need of any antibiotic and having re ceived none, and (3) being born from mothers who had not received any antibiotic during or after preg nancy. They were all fed with human milk provided by the lactarium (40/60) or with an artificial one (20/60) by bottle or by gastric-tube feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Strains spread in the hospital milieu contributed significantly to colonization (29). In developing countries, almost all infants acquire E. coli in the first week of life (30,31), including infants delivered by cesarean section (31,32) In the present study, we noted less than 50% E. coli colonization by 1 wk of age.…”
Section: Discussionsupporting
confidence: 42%
“…Domesticated animals are a potential source of human infections, and contamination of food by Escherichia coli from animals is widespread [1,2]. Analysis of the serotypes of human and animal E. coli strains from diarrheal diseases have indicated that they are distinct in most cases [3,4]. However, few studies show that there are E. coil clones which are pathogenic for both humans and animals.…”
Section: Introductionmentioning
confidence: 99%